Exploring the potential mechanisms of Shiwei Hezi pill against nephritis based on the method of network pharmacology - Wei, Lei (Frontiers in Pharmacology, 2023)
Objective: We aimed to reveal the potential active ingredients, targets and pathways of SHP in the treatment of nephritis based on systematic network pharmacology. Methods: The online database was used to screen the common targets of SHP and nephritis, and the interaction between targets was analyzed.GO functional annotation and KEGG pathway enrichment analysis were performed using the bioinformatics Website. Molecular docking techniques were carried out to verify the correlation between core ingredients and key targets. Cytoscape 3.6.1 was used to PPT network construction and data visualization. Results: A total of 82 active ingredients in SHP were screened, and 140 common targets of SHP and nephritis were obtained. Our results demonstrated that TNF, AKT1 and PTGS2 might be the key targets of SHP in the treatment of nephritis. GO enrichment analysis yielded 2163 GO entries (p<0.05), including 2,014 entries of the biological process (BP) category,61 entries of the cell composition (CC) category and 143 entries of the molecular function (MF) category. KEGG pathway enrichment analysis produced 186 signaling pathways (p<0.05), involving the AGE-RAGE, IL-17and TNF signaling pathways. The results of molecular docking showed that the three active ingredients of quercetin, kaempferol and luteolin could effectively bind to the three targets of TNF, AKT1 and PTGS2. Conclusions: The effective active ingredients in SHP may regulate multiple signaling pathways through multiple targets, thereby having a therapeutic effect on nephritis.